Bulk droplet vitrification: an approach to improve large-scale hepatocyte cryopreservation outcome - de Vries, Reinier J. (Langmuir, 2019)
Loss of hepatocyte viability and metabolic function after cryopreservation is still a major issue. Although vitrification is a promising alternative, it has generally been proven to be unsuitable for vitrification of large cell volumes which is required for clinical applications. Here we propose a novel bulk droplet (3 to 5 mm diameter) vitrification method which allows high throughput volumes (4 ml/min), while using a low pre-incubated CPA concentration (15% v/v) to minimize toxicity and loss of cell viability and function. We used rapid (1.25 s) osmotic dehydration in order to concentrate a low pre-incubated intracellular CPA concentration ahead of vitrification, without the need of fully equilibrating toxic CPA concentrations. We compared direct post-preservation viability, long-term viability and metabolic function of bulk droplet vitrified, cryopreserved and fresh hepatocytes. Simulations and cooling rate measurements confirmed an adequate concentration of the intracellular CPA concentration (up to 8.53 M) after dehydration in combination with high cooling rates (960 to 1320°C/min) for successful vitrification. Compared to cryopreserved hepatocytes, bulk droplet vitrified hepatocytes had a significantly higher viability, directly after preservation and after one day in culture. Moreover, bulk droplet vitrified hepatocytes had evidently better morphology and showed significantly higher metabolic activity than cryopreserved hepatocytes in long term collagen sandwich cultures. In conclusion, we developed a novel bulk droplet vitrification method of which we validated the theoretical background and demonstrated the feasibility to use this method to vitrify large cell volumes. Moreover, we showed that this method results in improved hepatocyte viability and metabolic function as compared to cryopreservation.